2010
DOI: 10.1074/jbc.m109.074583
|View full text |Cite
|
Sign up to set email alerts
|

PIASy Mediates SUMO-2/3 Conjugation of Poly(ADP-ribose) Polymerase 1 (PARP1) on Mitotic Chromosomes

Abstract: PIASy is a small ubiquitin-related modifier (SUMO) ligase that modifies chromosomal proteins in mitotic Xenopus egg extracts and plays an essential role in mitotic chromosome segregation. We have isolated a novel SUMO-2/3-modified mitotic chromosomal protein and identified it as poly(ADP-ribose) polymerase 1 (PARP1). PARP1 was robustly conjugated to SUMO-2/3 on mitotic chromosomes but not on interphase chromatin. PIASy promotes SUMOylation of PARP1 both in egg extracts and in vitro reconstituted SUMOylation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 35 publications
1
73
0
Order By: Relevance
“…SUMOylation of PARP-1, however, did not alter the activity or localization of the enzyme. Still, inhibition of the SUMO pathway strongly increases PARylation at mitotic chromosomes, demonstrating that these two posttranslational modifications harbour interconnected roles during chromosomal segregation [110].…”
Section: Text Box 1 Sumoylation Regulates Topoisomerase Iiα In Mitosismentioning
confidence: 99%
“…SUMOylation of PARP-1, however, did not alter the activity or localization of the enzyme. Still, inhibition of the SUMO pathway strongly increases PARylation at mitotic chromosomes, demonstrating that these two posttranslational modifications harbour interconnected roles during chromosomal segregation [110].…”
Section: Text Box 1 Sumoylation Regulates Topoisomerase Iiα In Mitosismentioning
confidence: 99%
“…46 SUMOylation appears to be important for remodeling of attachments of Topoisomerase II to chromatin 43 and for negative regulation of PARP1 activity against chromosomal substrates. 45 The biological role of Borealin SUMOylation is not clear. 46 Outer kinetochore and fibrous corona proteins that are confirmed SUMOylation targets include BubR1 (a SAC component), Nuf2 (a member of the Hec1 MT binding complex) and CENP-E (a plus end-directed MT motor) ( Table 1).…”
Section: Mukhopadhyay* and Mary Dassomentioning
confidence: 99%
“…Experiments in mitotic Xenopus egg extracts (XEEs) using GFP-SUMO-2/3 demonstrate considerable accumulation of SUMO-2/3 in the ICR region. 43 ICR components that are confirmed SUMOylation targets include Topoisomerase II, 44 poly(ADP-ribose) polymerase 1 (PARP1) 45 and the chromosome passenger complex component Borealin. 46 SUMOylation appears to be important for remodeling of attachments of Topoisomerase II to chromatin 43 and for negative regulation of PARP1 activity against chromosomal substrates.…”
Section: Mukhopadhyay* and Mary Dassomentioning
confidence: 99%
“…SUMO is conjugated to cellular substrates by an analogous pathway to that of ubiquitin. It has been reported that SUMOylation is mediated without E3 ligases in vitro (5,6), but under physiological conditions, SUMO E3 ligases are essential to execute SUMOylation of cellular substrates (7)(8)(9)(10). There are mainly two types of SUMO E3 ligases in vertebrates, RanBP2 (Nup358), and Siz/PIAS.…”
mentioning
confidence: 99%
“…For example, DNA topoisomerase II␣ (TopoII␣) and poly [ADP-ribose] polymerase I (PARP1) are each modified by SUMO2/3 in a PIASy-dependent manner during mitosis (9,20). Immunodepletion of PIASy completely abolishes mitotic chromosomal SUMOylation in Xenopus egg extracts (XEE) and other PIAS family proteins fail to restore this defect, indicating a unique role of PIASy in mitotic chromosomal SUMOylation in XEE (7).…”
mentioning
confidence: 99%